Experimentieren Einblicke in Praktiken und Versuchsaufbauten zwischen Wissenschaft und Gestaltung - Marguin, Séverine; Rabe, Henrike; Schäffner, Wolfgang; Schmidgall, Friedrich (Science Studies, 2019)
The volume offers an inventory of contemporary experimental cultures in the conflicting area between science and design and outlines a praxeology of the experiment.